COMBINATIONS OF ALLELES OF THE Ppd AND Vrn GENES DETERMINE THE HEADING TIME IN COMMON WHEAT VARIETIES - E. K. Potokina; V. A. Koshkin; E. A. Alekseeva; I. I. Matvienko; V. A. Filobok; L. A. Bespalova (Вавиловский журнал генетики и селекции)
Allele combinations of the Ppd-D1, Vrn-A1, Vrn-B1 and Vrn-D1 genes have been investigated with allele-specific primers in 56 wheat cultivars and breeding lines raised at the Lukyanenko Krasnodar Research Institute of Agriculture. A significant association between the allele combinations and heading dates has been detected, as well as an interaction between the genotype and day length. Allele-specific markers allow breeders to manipulate plant material and to choose allele combinations most suitable for particular growth conditions.